Injection Drug Use Cessation and Use of North America’s First Medically Supervised Safer Injecting Facility - DeBeck, Kora (Drug Alcohol Depend, 2010)
BACKGROUND: Vancouver, Canada has a pilot supervised injecting facility (SIF), where individuals can inject pre-obtained drugs under the supervision of medical staff. There has been concern that the program may facilitate ongoing drug use and delay entry into addiction treatment. METHODS: We used Cox regression to examine factors associated with the time to the cessation of injecting, for a minimum of six months, among a random sample of individuals recruited from within the Vancouver SIF. In further analyses, we evaluated the time to enrollment in addiction treatment. RESULTS: Between December 2003 and June 2006, 1090 participants were recruited. In Cox regression, factors independently associated with drug use cessation included use of methadone maintenance therapy (Adjusted Hazard Ratio [AHR] =1.57 [95% Confidence Interval [CI]: 1.02–2.40]) and other addiction treatment (AHR =1.85 [95%CI: 1.06–3.24]). In subsequent analyses, factors independently associated with initiation of addiction treatment included: regular SIF use at baseline (AHR =1.33 [95%CI: 1.04–1.72]); having contact with the addiction counselor within the SIF (AHR =1.54 [95%CI: 1.13–2.08]); and Aboriginal ancestry (AHR =0.66 [95%CI: 0.47–0.92]). CONCLUSIONS: While the role of addiction treatment in promoting injection cessation has been well described, these data indicate a potential role of SIF in promoting increased uptake of addiction treatment and subsequent injection cessation. The finding that Aboriginal persons were less likely to enroll in addiction treatment is consistent with prior reports and demonstrates the need for novel and culturally appropriate drug treatment approaches for this population.